Nontraditional sites for vascular anastomoses to enable kidney transplantation in patients with major systemic venous thromboses. Issue 12 (28th November 2017) - Lonze, Bonnie E.; Dagher, Nabil N.; Alachkar, Nada; Jackson, Annette M.; Montgomery, Robert A.
Abstract: Successful renal transplantation requires low‐pressure venous drainage to permit adequate outflow from the allograft. We report here a series of three patients in whom the inferior vena cava as well as bilateral iliac veins were thrombosed, making it necessary to explore less traditional vessels for venous drainage of the renal allograft. We utilized the splanchnic vasculature in two cases and the native left renal vein in another. The resulting atypical intra‐abdominal locations of these allografts also presented difficulties for arterial anastomoses and for urinary drainage. Arterial conduits were utilized in two cases to facilitate anastomosis to the common iliac artery or the aorta, and in the third case, the splenic artery was used for arterial inflow. A traditional ureterocystostomy was technically feasible for only one patient. In another, ureteroureterostomy to the native ureter was performed, and in the third case, the creation of an ileal conduit was necessary. All three patients had antibodies to human leukocyte antigens and two required desensitization. All three kidneys had immediate graft function and continued to function at 1 year post‐transplant. With a combination of planning, creativity, and persistence, patients with IVC thrombosis can enjoy the benefits of renal transplantation.